Hydrogen desorption improvement of the LiNH2–LiH–KF composite. (28th September 2016) - Dong, Bao-Xia; Gao, Jing-Jing; Tian, Hui; Teng, Yun-Lei; Wang, Long-Zheng; Liu, Wen-Long
Abstract: Interestingly, an obvious enhancement of the hydrogen storage property is achieved by introducing KF into the LiNH2 –LiH system, while KCl, KBr or KI does not show obvious effect on improving the hydrogen storage properties of the LiNH2 –LiH system. In comparison with that of the LiNH2 –LiH composite, the hydrogen desorption curve of the LiNH2 –LiH–0.05 KF composite becomes sharp and the dehydrogenation onset and peak temperatures are decreased by about 36 °C and 38 °C, respectively. The cyclic capacity and desorption kinetic of the LiNH2 –LiH–0.05 KF composite in the tenth cycle are still much better than that of the LiNH2 –LiH composite in the second cycle. Cyclic performance can be improved at least 4 times by addition of 5 mol% KF. Detailed structural investigations reveal that during the heat-treatment, the doped potassium fluoride can react with LiH and convert to potassium hydride, which induces the improvement in hydrogen storage properties of the LiNH2 –LiH system. Highlights: KF is effective to enhance hydrogen storage properties of LiNH2 –LiH system. Dehydrogenation onset and peak temperatures are decreased by about 36 °C and 38 °C. The reversibility of LiNH2 –LiH system is also improved drastically by addition of KF.